2002
DOI: 10.1074/jbc.m109135200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Cytoplasmic Domains in the Escherichia coli TatC Protein

Abstract: The twin-arginine translocation (Tat) system mediates the transport of proteins across the bacterial plasma membrane and chloroplast thylakoid membrane. Operating in parallel with Sec-type systems in these membranes, the Tat system is completely different in both structural and mechanistic terms, and is uniquely able to catalyze the translocation of fully folded proteins across coupled membranes. TatC is an essential, multispanning component that has been proposed to form part of the binding site for substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 31 publications
5
66
0
Order By: Relevance
“…This group of proteins shares a similar orientation in the membrane with N and C termini exposed to the cytoplasmic or stromal side of the membrane (20,44,50,51). Particularly, alignment of TatC proteins revealed that conserved residues are preferably localized in the region exposed to the cytosolic site (52,53). Mutagenesis of conserved positions of E. coli TatC has revealed that some of these residues are critical for its function, which would be consistent with a role in substrate binding (52,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group of proteins shares a similar orientation in the membrane with N and C termini exposed to the cytoplasmic or stromal side of the membrane (20,44,50,51). Particularly, alignment of TatC proteins revealed that conserved residues are preferably localized in the region exposed to the cytosolic site (52,53). Mutagenesis of conserved positions of E. coli TatC has revealed that some of these residues are critical for its function, which would be consistent with a role in substrate binding (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, alignment of TatC proteins revealed that conserved residues are preferably localized in the region exposed to the cytosolic site (52,53). Mutagenesis of conserved positions of E. coli TatC has revealed that some of these residues are critical for its function, which would be consistent with a role in substrate binding (52,53). Elucidated site-specific affinity of For E. coli TatC a dual topology has been suggested: Its calculated 6 transmembrane-spanning domains were confirmed by Behrendt et al (54).…”
Section: Discussionmentioning
confidence: 99%
“…Bolhuis et al (9) have constructed a TatB-TatC fusion protein by connecting the C terminus of TatB to the N terminus of TatC. Because the N terminus of TatC is located in the cytoplasm (20,35,36), the fusion should prohibit the C terminus of TatB changing the cellular location. Interestingly, the TatB-TatC fusion protein functionally complements a null mutant lacking both TatB and TatC in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to address this combines mutagenesis with biochemical characterization and protein-protein interaction studies. This approach has been conducted to some extent with the Escherichia coli Tat system (Allen et al, 2002;Buchanan et al, 2002;Barrett et al, 2005;McDevitt et al, 2006;Holzapfel et al, 2007), but not with the plant Tat system owing to the relative difficulty of mutagenesis and gene replacement.…”
Section: Introductionmentioning
confidence: 99%